Study Protocol of Sleep Education Tool for Children: Serious Game “Perfect Bedroom: Learn to Sleep Well” - Almondes, Katie Moraes de; Leonardo, Maria E. M. (Frontiers in Psychology, 2018)
Promoting a healthy sleep is a big challenge and becomes a strategic priority in public health, due to the severe consequences on children's development and risk to psychiatric diseases. Interventions that promote healthy sleep, such as those that focus on the dissemination of behavioral and environmental recommendations of sleep hygiene with children, are presented as an alternative. Serious game design offers wide-reaching domains in health applications and is increasing in popularity, particularly with children and teens because of it’s potential to engage and motivate players differently from other interventions. This study aims to evaluate effects of serious game on sleep hygiene recommendations "Perfect Bedroom: learn to sleep well", on sleep habits and sleep parameters of healthy children. This is an experimental, prospective and quantitative study. We will randomize children in experimental (n=88) and no intervention groups (n=88). The experiment has four stages (pre-intervention, intervention, post-intervention and follow-up), which will count with participation of children and their parents/guardians. In the evaluation stages, the guardians will answer questionnaires and scales to assess sociodemographic and health data, sleep habits and sleep pattern of their child. The children themselves will answer the following: a scale to assess sleepiness levels, a questionnaire to evaluate the serious game and the game itself, will characterize their bedroom and the activities they perform before sleep, with strategies developed by researches. Intervention with experimental group conducted with the serious game "Perfect Bedroom" will happen twice a week, for three weeks in a row, resulting in six sessions of fifty minutes each. Inferential analysis will be conducted for comparisons between groups and intragroups to measure effect of intervention in primary outcomes (sleep habits) and secondary outcomes (sleep parameters). We expect that the intervention with this game can provide valuable evidence to a new approach in promoting healthy sleep habits, with applications in clinical, educational and familiar settings, which could diminish future health issues and risk at psychiatric diseases, decreasing the social burden of treatments for these conditions in children.